The Association of Graph Literacy With Use of and Skills Using an Online Personal Health Record in Outpatient Veterans. (1st August 2016) - Ruiz, Jorge G.; Andrade, Allen D.; Hogue, Christie; Karanam, Chandana; Akkineni, Sisir; Cevallos, David; Anam, Ramanakumar; Sharit, Joseph
Abstract : Personal health records (PHRs) are intended to increase patients' access to and ownership over their health care information for self-management purposes. The purpose of this study was to determine the association of graph literacy with adoption of an online PHR and, among adopters with self-reported skills, the frequency of use and intent to return to use the PHR . We conducted a cross-sectional survey of veterans receiving outpatient care. We measured health literacy, numeracy, graph literacy, and Internet and PHR adoption and use. We compared subgroups of veterans using analyses of covariance. We used hierarchical logistic regression models to estimate the effects of the literacy variables on PHR use. A total of 600 veterans (age = 22–94) participated in the survey. After we adjusted for known covariates, we found that adopters of a PHR were more likely to demonstrate higher health and graph literacy than nonadopters. Among PHR adopters, self-reported frequent and skillful users were more likely to have higher graph literacy than lower frequency and less skillful users. Adopters with higher intentions to return to use the PHR were more likely to show lower graph literacy than those less likely to return to use the PHR. Inadequate graph literacy was associated with lower adoption of a PHR and, among users, with lower self-reported frequent use and skills . As PHR use becomes more widespread, stakeholders will need to consider patients' levels of graph literacy when implementing PHRs.